Сократите дробь 1)а+3√а/a - 9
2) m-12 √m+36/m-36

daniil326 daniil326    3   04.12.2021 01:58    2

Ответы
katyakirdina12 katyakirdina12  18.01.2022 19:24

Объяснение:

Для  любого  неотрицательного  числа  a справедливо,  что  

\sqrt{a}\ge0\ и\ (\sqrt{a})^2=a$$.

\displaystyle 1)\;\;\; \frac{a+3\sqrt{a} }{a-9}=\frac{(\sqrt{a})^2 +3\sqrt{a} }{(\sqrt{a})^2-3^2 } =\frac{\sqrt{a}(\sqrt{a}+3) }{(\sqrt{a}-3)(\sqrt{a}+3) } =\frac{\sqrt{a} }{\sqrt{a}-3 }

\displaystyle 2)\;\;\;\frac{m-12\sqrt{m}+36 }{m-36}=\frac{(\sqrt{m})^2-2*6*\sqrt{m}+6^2 }{(\sqrt{m})^2-6^2 } =\\\\=\frac{(\sqrt{m}-6)^2 }{(\sqrt{m}-6)(\sqrt{m}+6) } =\frac{\sqrt{m}-6 }{\sqrt{m}+6 }

Использованы формулы:

(a-b)²=a²-2ab+b²

a²-b²=(a-b)(a+b)

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра